If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 35x + -14 = 36x + -6 Reorder the terms: -14 + 35x = 36x + -6 Reorder the terms: -14 + 35x = -6 + 36x Solving -14 + 35x = -6 + 36x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-36x' to each side of the equation. -14 + 35x + -36x = -6 + 36x + -36x Combine like terms: 35x + -36x = -1x -14 + -1x = -6 + 36x + -36x Combine like terms: 36x + -36x = 0 -14 + -1x = -6 + 0 -14 + -1x = -6 Add '14' to each side of the equation. -14 + 14 + -1x = -6 + 14 Combine like terms: -14 + 14 = 0 0 + -1x = -6 + 14 -1x = -6 + 14 Combine like terms: -6 + 14 = 8 -1x = 8 Divide each side by '-1'. x = -8 Simplifying x = -8
| -18=x+20 | | 36x-14=36x-6 | | -22=11(2c-8) | | |-14|= | | (22-18)x(3+8)= | | x-24=6 | | 2(2)+3(4a)-4(3+3a)+3=0 | | 3y-24-6y+37= | | 4d^2-4d-80=0 | | x-8.8=-6.8 | | 2=2m+2+6m | | (q*q*q)-6(q*q)-21600=0 | | 12/3x5-16 | | 10-x/4x | | 6(2x+2)+15= | | -2/-1 | | 0=x^4-6x^3-x^2+20x | | 2.6-5.1=6.6 | | 3x/4-1/3(3x-6)=5/2(6-x/2) | | 6(2x^2-9x-18)=0 | | 8x/3-2x-6 | | 11x^3-x+9=x^3+45x^2+x | | 683+2x=53 | | 18-(2m+5)=4+2m-15 | | 6(4x+15)+13x-12= | | 31/5+x=6 | | a=-2(1.4c)+4c | | 18080-5x=8 | | -x-6y=-5 | | 21/5+x=6 | | 4(x-80)+10=-10 | | 4(5x+6)+7(12-x)= |